1996
DOI: 10.1074/jbc.271.31.18306
|View full text |Cite
|
Sign up to set email alerts
|

Protein-tyrosine Kinase Activation Is Required for Lipopolysaccharide Induction of Interleukin 1β and NFκB Activation, but Not NFκB Nuclear Translocation

Abstract: In human monocytes, interleukin 1␤ protein production and steady state mRNA levels are increased in response to lipopolysaccharide, predominantly as a result of increased transcription of the interleukin 1␤ gene. Expression of interleukin 1␤ and other cytokines, such as interleukin 6 and tumor necrosis factor ␣, has been shown to be dependent on the activation of the transcription factor, NFB. Since recent studies have shown that lipopolysaccharide-induced tyrosine kinase activation is not required for NFB nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 27 publications
4
50
0
Order By: Relevance
“…Our results in relation to IB␣ are consistent with a previous study on PBMCs isolated from control and XLA donors, who have an inactive Btk, where it was observed that LPS-induced IB␣ degradation was intact in XLA PBMCs, but the induction of the NFB-dependent gene TNF was impaired (7). In addition, the general protein-tyrosine kinase inhibitor genistein, which has been shown to affect Btk (22), was shown not to inhibit LPS-activated NFB nuclear translocation as measured by DNA binding assays but blocked the induction of IL-1␤, again consistent with a lack of a role for tyrosine kinases in activating IB␣ degradation (23,24). The role of serine 536 phosphorylation in coupling p65 to coactivators, corepressors, or components of the basal tran- scriptional machinery has recently been investigated.…”
Section: Discussionmentioning
confidence: 49%
“…Our results in relation to IB␣ are consistent with a previous study on PBMCs isolated from control and XLA donors, who have an inactive Btk, where it was observed that LPS-induced IB␣ degradation was intact in XLA PBMCs, but the induction of the NFB-dependent gene TNF was impaired (7). In addition, the general protein-tyrosine kinase inhibitor genistein, which has been shown to affect Btk (22), was shown not to inhibit LPS-activated NFB nuclear translocation as measured by DNA binding assays but blocked the induction of IL-1␤, again consistent with a lack of a role for tyrosine kinases in activating IB␣ degradation (23,24). The role of serine 536 phosphorylation in coupling p65 to coactivators, corepressors, or components of the basal tran- scriptional machinery has recently been investigated.…”
Section: Discussionmentioning
confidence: 49%
“…Whether these phosphorylation events have the same functional outcome or whether they may lead to distinct functions is presently unclear. Recent data from our laboratory (30) and others (31) demonstrate that several inducers can control the transcriptional function of NF-B, independent of induced nuclear translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Dominant negative mutants of these small GTPases were generated by overlap extension as described elsewhere (31). Cdc42N17 was generated by replacing Thr 17 with Asn employing the overlapping primers 5Ј-GTAAAAACTGTCTCCTGATATCCTAC and 5Ј-GATATCAGGAGA-CAGTTTTTACCAACAGCACC, Rac1N17 was generated by replacing Thr 17 with Asn using the primers 5Ј-CTGTAGGTAAAAACTGCCTACT-GATC and 5Ј-TGATCAGTAGGCAGTTTTTACCTACAGCTCCG, and RhoAN17 was generated by replacing Thr 19 with Asn using the primers 5Ј-GTGGAAAGAACTGCTTGCTCATAGTCTTC and 5Ј-ATGAGCAAG-CAGTTCTTTCCACAGGCTCCATC (the underlined base triplet indicates the mutated amino acid). The Raf-1 dominant negative mutant encompassing the first 259 amino acids encoding the regulatory domain (32) was generated by polymerase chain reaction using full-length human Raf-1 (ATCC 41050) as template.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, inhibition of p38 mitogen-activated protein kinase (p38 MAPK) has been shown to decrease TNF-␣-induced NF-B activity and interleukin-6 expression (16). More recently, tyrosine phosphorylation has been shown to be essential for NF-B activity in bacterial lipopolysaccharide (LPS)-induced monocytic THP1 cells (17). Regulation of NF-B activity by PKC, extracellular signal-regulated kinase 1, p38 MAPK, or tyrosine phosphorylation acts downstream of IB without interfering with NF-B nuclear translocation and DNA binding.…”
mentioning
confidence: 99%